Biocompatibility and photo-induced antibacterial activity of lignin-stabilized noble metal nanoparticles. Issue 70 (4th December 2018) - Rocca, Diamela María; Vanegas, Julie P.; Fournier, Kelsey; Becerra, M. Cecilia; Scaiano, Juan C.; Lanterna, Anabel E.
Abstract : Natural derived compounds, lignins, can be used as reducing and stabilizing agents to synthesize noble metal nanoparticles with antimicrobial properties. Abstract : One-pot thermal and photochemical syntheses of lignin-doped silver and gold nanoparticles were developed and their antimicrobial properties were studied against Escherichia coli and Staphylococcus aureus . The nature of the lignin as well as the metal are directly involved in the antimicrobial activity observed in these nanocomposites. Whereas one of the nanocomposites is innocuous under dark conditions and shows photoinduced activity only against Staphylococcus aureus, the rest of the lignin-coated silver nanoparticles studied show antimicrobial activity under dark and light conditions for both bacteria strains. Additionally, only photoinduced activity is observed for lignin-coated gold nanoparticles. Importantly, the particles are non-cytotoxic towards human cells at the bactericidal concentrations. Preliminary assays show these silver nanoparticles as potential antimicrobial agents towards S. aureus biofilm eradication.